2023
DOI: 10.1177/13558196221149929
|View full text |Cite|
|
Sign up to set email alerts
|

Family physician services and blood pressure control in China: A population-based retrospective cohort study

Abstract: Objective Given the importance of continuous family physician (FP) care in the management of hypertension, we explored the effects of such care among hypertensive patients in China, a country where such care is generally underutilized. We examined the longitudinal association between the use and continuity of FP services and health outcomes including blood pressure (BP) control rate, systolic blood pressure (SBP), and diastolic blood pressure (DBP). Methods We conducted a population-based cohort study using da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As for China, most relevant domestic studies have focused on residents' awareness of family physician contract services, willingness to contract, factors infuencing the contract decision, and the implementation of family physician contract service systems [28][29][30]. In addition, several studies have indicated that compared with the reference group of patients without a family physician, hypertensive patients who receive care from their own contracted family physicians have a higher BP control rate [31]. Te family physician contract services policy also appeared to infuence the perceived participation of patients in their healthcare [32].…”
Section: Introductionmentioning
confidence: 99%
“…As for China, most relevant domestic studies have focused on residents' awareness of family physician contract services, willingness to contract, factors infuencing the contract decision, and the implementation of family physician contract service systems [28][29][30]. In addition, several studies have indicated that compared with the reference group of patients without a family physician, hypertensive patients who receive care from their own contracted family physicians have a higher BP control rate [31]. Te family physician contract services policy also appeared to infuence the perceived participation of patients in their healthcare [32].…”
Section: Introductionmentioning
confidence: 99%